Helicobacter pylori and lung function, asthma, atopy and allergic disease--a population-based cross-sectional study in adults. - Fullerton, D; Britton, JR; Lewis, SA; Pavord, I; McKeever, T; Fogarty, A (2009)
BACKGROUND: Exposure to microbes may result in the polarization of the immune system and a decrease in the risk of asthma and associated allergic disease, whilst exposure to Helicobacter pylori has been hypothesized to increase the risk of obstructive airways disease. We tested the hypotheses that exposure to H. pylori reduces the risk of asthma and allergic disease and is associated with a decrease in lung function. METHODS: Data were collected on allergic disease symptoms, forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), bronchial reactivity, allergen skin sensitization, serum IgE and H. pylori serological status in 2437 randomly selected adults. RESULTS: Individuals with serological evidence of exposure to H. pylori had lower lung function, FEV1 being lower by 53 ml (95% CI 1-106) and FVC 83 ml (95% CI 20-145) lower in the cross-sectional analysis. These differences ceased to be statistically significant after adjustment for height or socio-economic status. There was no association between H. pylori serological status and measures of asthma or atopy in the cross-sectional analysis, and there was no significant association between H. pylori serological status and decline in FEV1 and FVC over 9 years. CONCLUSION: Although H. pylori exposure may be associated with lower cross-sectional FEV1 and FVC, this association was not independent of height or socio-economic status. There was no association between H. pylori exposure and either chronic obstructive pulmonary disease (COPD), measures of allergic disease or decline in lung function.